# Solve for y square root of 8y+4 = square root of 7y+6

8y+4=7y+6
To remove the radical on the left side of the equation, square both sides of the equation.
8y+42=7y+62
Simplify each side of the equation.
Multiply the exponents in ((8y+4)12)2.
Apply the power rule and multiply exponents, (am)n=amn.
(8y+4)12⋅2=7y+62
Cancel the common factor of 2.
Cancel the common factor.
(8y+4)12⋅2=7y+62
Rewrite the expression.
(8y+4)1=7y+62
(8y+4)1=7y+62
(8y+4)1=7y+62
Simplify.
8y+4=7y+62
Rewrite 7y+62 as 7y+6.
Use axn=axn to rewrite 7y+6 as (7y+6)12.
8y+4=((7y+6)12)2
Apply the power rule and multiply exponents, (am)n=amn.
8y+4=(7y+6)12⋅2
Combine 12 and 2.
8y+4=(7y+6)22
Cancel the common factor of 2.
Cancel the common factor.
8y+4=(7y+6)22
Divide 1 by 1.
8y+4=(7y+6)1
8y+4=(7y+6)1
Simplify.
8y+4=7y+6
8y+4=7y+6
8y+4=7y+6
Solve for y.
Move all terms containing y to the left side of the equation.
Subtract 7y from both sides of the equation.
8y+4-7y=6
Subtract 7y from 8y.
y+4=6
y+4=6
Move all terms not containing y to the right side of the equation.
Subtract 4 from both sides of the equation.
y=6-4
Subtract 4 from 6.
y=2
y=2
y=2
Solve for y square root of 8y+4 = square root of 7y+6

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top